Sum cu paʼi yaṅ sñiṅ legs bśad ljon paʼi dbaṅ po bźugs so - Dbyaṅs-can-grub-paʼi-rdo-rje, Dṅul-chu, 1809-1887 (s.n., 1970)
Concise commentary on Sum cu pa, Tibetan grammatical treatise by Thon-mi Sambhota.